Allowing for Nondisclosure in High Suicide Risk Groups. (April 2020) - Podlogar, Matthew C.; Joiner, Thomas E.
Inaccurate disclosure of information is a significant limitation when relying on self-report for suicide risk screening. However, allowing for an explicit nondisclosure response option in screening items (e.g., "prefer not to disclose") may ultimately improve follow-up assessment validity. This study investigated explicit nondisclosure in suicide risk screening among military service members and veterans ( n = 135), men older than 50 years, ( n = 187), and LGBTQ (lesbian, gay, bisexual, transgender, or queer) young adults ( n = 140); all higher risk and lower help-seeking populations. Results indicated that allowing for explicit nondisclosure minimally affected screening sensitivity and specificity. However, its selection was prevalent among higher risk participants, and was associated with experience of past unhelpful reactions and "avoidance of stigmatized consequences." Allowing for nondisclosure creates potential psychometric and classification advantages, and may be a safe and effective way to encourage discussion of barriers, build trust, maximize patient autonomy, and ultimately facilitate accurate risk disclosure to improve assessment validity.